CONTRAST - INDUCED NEPHROPATHY, OLD STORY - NEW TWISTS - Brovina, Lulzim; Trajceski, Ted; Simonovski, Koco; Trajceska, Lada (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Aim: Radiological procedures utilizing intravascular iodinated contrast media are being widely applied for both diagnostic and therapeutic purposes and represent one of the main causes of contrast-induced nephropathy (CIN).In this hospital-based study we tried to assess predictors for development of CIN in patients undergoing cardiac catheterization.   A total of 5604 patients undergoing coronary angiogram/PCI from 2007-2017 were enrolled in the study. Multivariate predictors of CIN were identified by logistic regression using stepwise selection with entry and exit criteria of p < 0.1. A two-sided 95% confidence interval (CI) was constructed around the point estimate of the odds (OR). A p value <0.05 was considered significant. CIN occurred in 6 (1â€°) patients. The mean age of patients suffering from CIN was higher than in the whole population (66.5Â± 31.15 vs . 58.66Â± 28.57, p=0.03). Characteristics of patients who developed CIN were: older age, diabetes, higher creatinine and lower EF. The incidence of CIN in patients with diabetes was higher and statistically significant (84% vs . 16%, p=0.01).  Emergency cases were at higher risk of developing CIN than elective patients (85% vs. 15%, p=0.001), respectively. Diabetes, CKD and EF < 50% were independent predictors of CIN (RR 2.4, 95% CI: 1.88 - 7.132, p=0.008; RR 3.1, 95% CI: 2.17 - 6.682, p=0.003; RR 1.6, 95% CI: 2.88 - 7.132, p=0.01, respectively).The development of contrast-induced nephropathy in patients who underwent angiography and PCI was mainly related to older age, diabetes, lower GFR and heart failure, but not contrast material exposure.